The effect of customer experience and emotional value on the net promoter score: Middle-class millennial climber category - Syafrida Hafni Sahir; Syafrizal Helmi Situmorang (Jurnal Manajemen dan Pemasaran Jasa, 2020)
This study investigates net promoter score changes due to the emotional value and experience of middle-class customers. A total of 150 respondents wereselected, while 96 brands were observedbased on the respondent's daily life needs, such as clothes, cafes, gadgets and travels, amongothers. Customers experience was measured by analyzing their interactions with the brands they use. The emotional value was measured by the positive or negative emotion score of each brand. The gap between brand Promoter and Detractor is the Net Promoter Score. Thisresearch shows a positive correlation between customer experience, emotional value, and net promoter score. Data were analyzed using the Multiple regression method.